Momento hermeneútico del juez constitucional - Cambronero Torres, Andrei (2013)
This essay analyzes two pronouncements by the Constitutional Court, providing a conflict solution based on the content that “fills” the legal rules, just to reflect that hermeneutic practice pertaining to the legal function has no recipes, no univocal patterns, but just one subject who judges. Furthermore, it defends “judicio” as the common ground of technical factors, personal convictions, “prejudice” and “pre-conceptions”, as a result of an interpretation of the law propitiously “flawed” by external non-juridical elements.